ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS XI MIPA SMA NEGERI 1 KOTA JAMBI - ayu yarmayani (Universitas Batanghari Jambi, 2016)
This study aimed to describe the mathematical problem solving ability of students in a linear program material. The results of the research would be useful to optimize the mathematical ability of students to obtain good learning outcomes. In addition, this study may provide information to teachers how students' mathematical problem solving ability so it can construct a way of learning that can improve the ability of solving mathematical problems. This research is descriptive qualitative study aimed to describe the students' mathematical problem solving ability. Collecting data in this study conducted by way of mathematical problem solving ability test were then interviewed research subjects in accordance with the answers to the test. The Subjects of study is a class XI student of Mathematics 6 SMA Negeri 1 Kota Jambi first semester of academic year 2016/2017.Solving in mathematics is the process of finding the answer to a question contained in a narrative, text, tasks and situations in everyday life. Polya said solving the problem is just one aspect of higher level thinking as the process of accepting the problem and try to resolve the issue. In addition, problem-solving is an intellectual activity to seek to address the problems encountered with the use of the stock of knowledge already possessed. In such a condition is said to be a target problem-solving learning, students should be able to solve mathematical problems related to the real world. Based on the results of research on the analysis of mathematical problem solving ability can be concluded that the subject has the ability in solving problem solving. The initial step in the completion of subject matter that is to understand the problems presented by the question, the students write down what is known, asked and lack of any data to solve the problem . Indicators are still many students who have not been precise and systematic, mostly due to inaccuracies in the writing subject is not systematic problem solving. However, the subject has used the ability to think fast, clear and precise calculations in problem solving has been good.